MILITARY-POLITICAL CONFRONTATION BETWEEN THE RUSSIAN FEDERATION AND THE NATO MEMBER STATES IN THE BALTIC REGION - TSEPENDA, IGOR (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
This article analyses a range of problems faced by the NATO member states in the Baltic region in connection with Russian aggression in Ukraine. It is indicated that the Russian Federation boosts its military presence in the Kaliningrad Oblast: it deploys advanced missile systems and armored fighting vehicles to the region, increases its military contingent and rearms its Navy in the Baltic Sea. It is stressed that Russia has violated the 1987 Treaty on the Elimination of Intermediate-range and Shorter-range Missiles (the INF Treaty) and in recent years has been conducting large-scale military exercises. It is pointed out that amid the growing threat from Russia, the countries of the Baltic region have to reconsider their military strategies, to join their efforts in order to prevent any possible aggression. The NATO member states, the United States of America in particular, take part in the military drills in the region. Sweden’s military cooperation with NATO and the United States of America – a controversial issue in Swedish political circles – is discussed. The question of enhancing military interaction between the members of NATO – Germany and Norway, the Unites States and Poland – is addressed too. The advantages of building collective missile defense capability in the Baltic region and taking other steps to restrain Russia’s aggressive actions are indicated.